Incarcerated small bowel within a spontaneous lumbar hernia - Teo, K. A. T.; Burns, E.; Garcea, G.; Abela, J. E.; McKay, C. J. (Hernia : the journal of hernias and abdominal wall surgery, 2010)
Lumbar hernias are rare, resulting from protrusion through the posterior abdominal wall that may be congenital, acquired or spontaneous. They very rarely present with acute bowel obstruction. We present a case of incarcerated small bowel within a spontaneous inferior (Petit’s) lumbar hernia, treated by early open repair with mesh insertion. This case highlights the importance of thorough clinical examination and a high index of suspicion, even in the absence of previous surgery around the anatomical site of the suspected hernia, in order to effect an early repair before the onset of ischaemia in incarcerated contents.